The APT Frequency Arrangement in the 700 MHz: Reflections on the International Spectrum Management Regime - El-Moghazi, Mohamed; Whalley, Jason; Irvine, James (Journal of Telecommunications and the Digital Economy, 2016)
Following WRC-12, discussions have emerged with regard to the frequency arrangements in the 700 MHz band, out of band emissions (OOBE) of the mobile terminals below 694 MHz considering the allocation of the 694-790 MHz band to the mobile service. These discussions have shown that there is a tendency to partially harmonise with the APT plan and to adopt APT OOBE values. This reflects the emerging approach of countries in Regions 1 and 2 that are aligning themselves with Region 3 to lower the cost of end user equipment. Countries such as Australia and New Zealand are leading the discussion in Region 3. The 700 MHz issue has revealed that the ITU-R decision making procedures are mostly based upon consensus with the possibility of few countries blocking the discussion. Moreover, it suggests that there is a need to revise the current ITU-R structure of three regions.